Strategi Promosi Potensi Unggulan Dalam Meningkatkan Investasi Daerah Kabupaten Bima Provinsi NTB (Studi Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Bima) - Nurwahidah, Nurwahidah; Iswan, Iswan; suryaningsih, suryaningsih; Dhea Chandra Dewi, Dhea Chandra Dewi (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2025)
Regional economic development is an integral part of national development. One of the key factors in regional development is the inflow of investment, both domestic and foreign. Investment acts as a catalyst for economic growth as it creates job opportunities, increases community income, and accelerates infrastructure development. Bima Regency possesses various superior potentials that serve as investment attractions, including the agriculture, fisheries, livestock, and tourism sectors. In this context, the role of the Investment and One-Stop Integrated Services Office (DPMPTSP) of Bima Regency becomes crucial. As the agency responsible for licensing services and investment promotion, DPMPTSP is required to design and implement promotional strategies that are accurate, efficient, and oriented toward regional advantages. This research employs a qualitative descriptive approach aimed at providing an in-depth overview of the investment promotion strategies implemented by DPMPTSP Bima Regency. Primary data were obtained directly through interviews and observations, while secondary data were drawn from official documents. The findings indicate that the promotional strategies currently implemented still require reinforcement in both substantive and technical aspects. In terms of investment realization, there was a significant increase and shift between 2023 and 2024. The year 2023 was dominated by Domestic Investment (PMDN) in the trade sector, while 2024 saw a sharp increase in Foreign Investment (PMA) in the tourism sector. This reflects a shift in investment patterns and the success of promoting newly prioritized sectors, although further strengthening of long-term strategies remains necessary.